"L\\{y''+2y'+2y\\}=L\\{2\\}"
"(-y'(0)-sy(0)+s^2Y(s))+2(-y(0)+sY(s))+2Y(s)=\\dfrac{2}{s}"
Inserting the initial conditions and rearranging:
"Y(s)(s^2+2s+2)=\\dfrac{2+s}{s}"
"Y(s)=\\dfrac{2+s}{s(s^2+2s+2)}"
"\\dfrac{2+s}{s(s^2+2s+2)}=\\dfrac{A}{s}+\\dfrac{Bs+C}{s^2+2s+2}"
"=\\dfrac{As^2+2As+2A+Bs^2+Cs}{s(s^2+2s+2)}"
"s=0:2=2A=>A=1"
"s^2:A+B=0=>B=-1"
"s^1:2A+C=1=>C=-1"
"Y(s)=\\dfrac{1}{s}+\\dfrac{s-1}{s^2+2s+2}"
"y(t)=L^{-1}\\{Y(s)\\}=L^{-1}\\{\\dfrac{1}{s}-\\dfrac{s+1}{(s+1)^2+1}\\}"
"=1-e^{-t}\\cos t"
Comments
Leave a comment